Characteristics and Influence of Squall Line on Moderate to Heavy Rain Phenomenon in Jambi Province - Herdyansyah HB, M Randy; Syarifuddin , Hutwan; Saad, Asmadi (Rifa'Institute, 2025)
Introduction: Jambi Province is a region prone to moderate to heavy rainfall events that are often triggered by mesoscale convective systems such as squall lines. This study aims to analyze atmospheric conditions, squall line characteristics, and their impact on surface rainfall. Three squall line events on May 7, 2024, June 21, 2024, and May 17, 2025, were selected as case studies. Methods: The research methods include analysis of 3000 ft wind data, 850–500 mb layer humidity, 925 mb air pressure, Himawari-08/09 satellite imagery, weather radar data, and AWS rainfall. Radar data were processed using Rainbow software, while satellite data were analyzed using Sataid. Results and Discussion: The results show that the three squall line events are supported by high air humidity (70–90%), wind deflection, and a low pressure center along Sumatra. Weather radar is able to clearly display the formation and decay of squall lines, with a linear convective structure that is not detected by satellite imagery. Measured rainfall varied from light to heavy rain in areas crossed by the squall line. Conclusion: Weather radar is the most effective instrument in identifying the squall line in Jambi, while satellite imagery only supports monitoring convective clouds. These results are important as a basis for improving the accuracy of early warnings for extreme weather.